a week ago Grade -10 (SEE) Math

Solve this equation 5(- 3x – 2) – (x – 3) = -4(4x + 5) + 13

Please solve this algebra question (find the value of x) from class 8 
5(- 3x - 2) - (x - 3) = -4(4x + 5) + 13

1 Answer

a week ago Tribhuvan University > Institute of Science and Technology > B.Sc. (CSIT)

Given the equation
5 (- 3 x - 2) - (x - 3) = - 4 (4 x + 5) + 13


Multiply factors.
-15 x - 10 - x + 3 = - 16 x - 20 + 13


Group like terms.
- 16 x - 7 = - 16 x - 7


Add 16x + 7 to both sides and write the equation as follows
0 = 0
The above statement is true for all values of x and therefore all real numbers are solutions to the given equation.

Like Us On Facebook

World केस : 18732121 , मृत्यु : 705029

USA केस : 4918789 , मृत्यु : 160326

India केस : 1910681 , मृत्यु : 39856

Nepal केस : 21009 , मृत्यु : 58